THE CORRELATION BETWEEN STUDENTS’ MOTIVATION AND ANXIETY IN SPEAKING AT SMPN 3 JANAPRIA - Muh Madyan Sufyan Hadi; Tri Setianingsih; I Made Permadi Utama (E-LINK JOURNAL, 2018)
This study is generally attempted to find out whether there is or there is not the correlation between students’ motivation and anxiety in speaking for second grade students of SMPN 3 Janapria in academic year 2018/2019. The method of this research was applied correlative research. The population of this research was second grade students of SMPN 3 Janapria which consisted of 22 students, 11 male and 11 female. The technique which used to analysis the data was test formula. From the result of the data found out the score ofr count = 0,334. If the error level is set in 5%, and N = 22 so the r table =  0,423. It means r count is lower than r table or 0,334 ≤ 0,423. Therefore the alternative hypothesis is rejected. In other word there is no significant correlation between students’motivation and anxiety in speaking for second grade students of SMPN 3 Janapria. Key Words: Motivation, Anxiety, Speaking.